KORELASI ANTARA PERKEMBANGAN MOTORIK HALUS DENGAN PEMBERIAN ASI EKSKLUSIF PADA BALITA - Dhiyan Nany Wigati; Rizki Sahara (Journal Of Applied Health Research And Development, 2020)
Many benefits are obtained from breastfeeding (ASI). Breast milk is the main source of nutrition for babies who have not been able to digest solid food. Babies who are breastfed will get the best nutrition that cannot be replaced even by the best formula milk. To achieve optimal baby growth and development, exclusive breastfeeding needs to be given to newborns until the age of six months and can be continued until children are 2 years old. Breast milk is enough to maintain the growth of the baby until the age of 6 months. No other food is needed during this time. This study aims to determine the correlation between fine motor development with exclusive breastfeeding in children. This study uses an analytic observational research design. Distributing questionnaires and observations using the Denver II sheet. Analysis technique to test hypotheses using Spearman Correlation with SPSS. The results of analysis using the Spearman correlation obtained values sig. 0,025 where 0,025<0,05 which can be concluded that there is a significant correlation between fine motor development with exclusive breastfeeding in children with moderate levels of correlation. Lactation counseling is needed for breastfeeding mothers to ensure that children can grow and develop optimally